Challenges regarding the provision of antibiotics via the informal sector across low- and middle-income countries and potential ways forward - Maluleke, Tiyani Milta; Ur Rehman, Inaam; Kurdi, Amanj; Godman, Brian; Meyer, Johanna C (Journal of the Medical College for Women & Hospital, 2026)
Abstract not available J Med Coll Women Hosp.2026; 22(1): 14-30